Analysis of residential choice behavior at community scale - Masaya Kawano; Tetsunobu Yoshitake; Hiroshi Tatsumi; Yoshitaka Kajita (European Regional Science Association (ERSA), 2004)
The complex problems shared by many cities throughout Japan are evidence of the impacts of land use plans that have been poorly designed and managed. Most of the existing plans in Japan have focused on the metropolitan areas but nowadays the physical layout or land use of communities is fundamental to sustainability. Community sustainability requires a transition from poorly-managed large-scale plans to land use planning practices at the community scale that maintain efficient infrastructures, and ensure close-knit neighborhoods and a sense of community. This paper provides a scheme for discussing the residential choice of people at the community scale in a local city in Japan in order to help local communities or local authorities concerned with suitable land use planning. First, this paper gives the key principles of residential choice behavior through the statistical analysis of the revealed preference of people who actually made the decision to choose the location of their new residence. Some interesting results are a bigger correlation than expected between the location of residence and the place of work, and a strong attachment of movers to their old communities. The latter half of this paper describes a modeling process for specifying the residential choice at the community scale. The discrete choice model adopted in the present study is a conventional disaggregate logit model that is capable of representing complicated individual choice behavior while they are changing their place of residence.
Keywords: 330